A Study of Grammatical Errors in Descriptive Writing Paragraphs Made by the Second Semester Students of English Education Department of Universitas Islam Malang (UNISMA) - Nilam Esti Lestari (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
Abstract: There are still many students who make errors when they compose a text. It is understandable for students of foreign language learners. Error analysis is needed for teacher to increase student’s ability in writing especially in grammatical use. This study figured out students’ grammatical errors in descriptive writing paragraphs and aimed to examine the most errors that students made.The design of this research was descriptive qualitative to analyze the students’ descriptive writing paragraphs. The subjects of this research were students in second semester of English Department of Universitas Islam Malang in the academic years 2019-2020. By using Dulay’s theory that is Surface Strategy Taxonomy which classify into omission error, addition error, misformation error, and misorder error, the students’ descriptive writing paragraph is identified.From the 21 data of students’ descriptive writing paragraphs, grammatical errors found in second semester students of English Department of Unisma. Based on the research analysis, 73 total errors are found. All of errors contains of omission, addition, misformation, and misorder errors. After analyzed the data, the researcher found each types of errors as follows; omission error (47.13%), misformation errors (24.66%), addition error (19.18%), misorder error (10.95%). The example of omission error is omissing the article as like “the/a/an”. Contrast to omission error, the sample of addition error is adding double mark as like put a same word in a sentence which is unnecessary. The other error is misformation with the example of misformation verb that is “Panda” is singular noun which should use verb “has” but the student use “have”. Another error is misorder error. Although this is the fewest error found, some students wrote the wrong placement of word, for example “Unisma is bigger one of university of Nahdhotul Ulama (NU) in Indonesia”.In this case the researcher found some sources of error that students made. The first is interlingual transfer occurs when the students transfer their native language into target language. Another source of error is context of learning because the students have understood by memorizing the grammatical rule, but they get failure to apply in making a textBased on the research above, the researcher gives suggestions for the students, the teacher, and the future researcher. The students should pay attention to the teacher’s explanation and correct their work before submit it. For the teacher, they should give more explanations to the students about grammatical use in order to increase students’ writing skill. And also the researcher hopes for the future researcher to expand error analysis research. keywords: analysis,grammartical error, Descriptive text